Quantitative hopanoid analysis enables robust pattern detection and comparison between laboratories. Issue 4 (11th April 2015) - Wu, C.‐H.; Kong, L.; Bialecka‐Fornal, M.; Park, S.; Thompson, A. L.; Kulkarni, G.; Conway, S. J.; Newman, D. K.
Abstract Hopanoids are steroid‐like lipids from the isoprenoid family that are produced primarily by bacteria. Hopanes, molecular fossils of hopanoids, offer the potential to provide insight into environmental transitions on the early Earth, if their sources and biological functions can be constrained. Semiquantitative methods for mass spectrometric analysis of hopanoids from cultures and environmental samples have been developed in the last two decades. However, the structural diversity of hopanoids, and possible variability in their ionization efficiencies on different instruments, have thus far precluded robust quantification and hindered comparison of results between laboratories. These ionization inconsistencies give rise to the need to calibrate individual instruments with purified hopanoids to reliably quantify hopanoids. Here, we present new approaches to obtain both purified and synthetic quantification standards. We optimized 2‐methylhopanoid production in Rhodopseudomonas palustris TIE‐1 and purified 2Me‐diplopterol, 2Me‐bacteriohopanetetrol (2Me‐BHT), and their unmethylated species (diplopterol and BHT). We found that 2‐methylation decreases the signal intensity of diplopterol between 2 and 34% depending on the instrument used to detect it, but decreases the BHT signal less than 5%. In addition, 2Me‐diplopterol produces 10× higher ion counts than equivalent quantities of 2Me‐BHT. Similar deviations were also observed using a flame ionization detector for signal quantification in GC. In LC‐MS, however, 2Me‐BHT produces 11× higher ion counts than 2Me‐diplopterol but only 1.2× higher ion counts than the sterol standard pregnane acetate. To further improve quantification, we synthesized tetradeuterated (D4) diplopterol, a precursor for a variety of hopanoids. LC‐MS analysis on a mixture of (D4)‐diplopterol and phospholipids showed that under the influence of co‐eluted phospholipids, the D4‐diplopterol internal standard quantifies diplopterol more accurately than external diplopterol standards. These new quantitative approaches permit meaningful comparisons between studies, allowing more accurate hopanoid pattern detection in both laboratory and environmental samples.